INTERACTIONS OF STUDENT AND SUPERVISOR IN SKRIPSI RESEARCH: UNDERSTANDING DIFFERENCES IN PERSPECTIVES AND EXPECTATION - Fitri, Sarah (PEOPLE: International Journal of Social Sciences, 2017)
Skripsi is a term used to describe a scientific research paper written by undergraduate students as a mandatory requirement to complete their study at a higher education institution in Indonesia. The process of producing a skripsi is complex and demanding. One of the most important and profound issues in skripsi is student’s interaction with skripsi supervisor. Even though the role of supervisor is important in assisting students’ skripsi process, there seems to be issues regarding their interaction with students. The purpose of this study is to understand interactions of students and superviors in skripsi and its challenges and to find out their perspectives and expectations while working on it. The author distributed online survey and conducted in-depth interview to twenty students and faculty members of UIN Ar-Raniry, Indonesia. The findings showed that there are prominent issues found in skripsi process and the conduct of it. The response also indicated that complex procedure, limitation of time, and different expectation lead to issues related to students’ interactions with their supervisors. Based on the findings, this paper emphasizes on the necessity for mutual understanding to improve the skripsi process and suggests for additional way (online assistance) to increase communication and interactions between students and supervisors.